Diagnosis of Students’ Difficulties in Balancing Chemical Equations in Some Selected Senior Secondary Schools in Ibadan, Nigeria - OGUNDIJI, Olasunkanmi (MASI Mandiri Edukasi, 2024)
Researchers are concerned about students' difficulties in balancing chemical equations and are working to correct these inaccuracies. The survey identified difficulties among science students in public senior secondary schools in Ibadan, Nigeria. A descriptive research design was used; 188 respondents from six public senior secondary schools in Ibadan provided data for the study. The Chemical Equation Diagnostic Test was developed and validated utilizing test-retest methodology (r=0.86). The data demonstrates the incapacity of students to identify limiting reagents (96.56%), reactants in a reaction (48.4%), understand moles (76.1%), understand atomicity (79.3%), determine the number of elements present in a compound (22.9%); identify the physical states of elements (54.3%); and calculate the valency of elements (79.3%). According to the outcome, students have several difficulties balancing chemical equations. It is advised that teachers diagnose such difficulties by recognizing the numerous ways students struggle to balance chemical equations. Addressing such difficulties will reduce students’ misconceptions about chemistry, improve their conceptual knowledge of chemistry, and increase the number of students who may wish to pursue advanced courses in chemistry and science-related fields.